Early life obesity increases the risk for asthma in San Francisco born Latina girls - McCallister, Margaret (Allergy Asthma Proc, 2018)
BACKGROUND: Previous studies showed that youths who are obese are more likely to have asthma; however, some studies found important sex differences in the risk for asthma. METHODS: We retrospectively assessed the asthma incidence in a Latino cohort of children recruited from birth and followed up until 9 years of age. We subsequently assessed risk factors for asthma and for an early asthma (defined as <4 years of age) diagnosis in relation to obesity. Asthma was assessed via maternal reports and medical records review of the children at 9 years of age. Each child's weight and height were collected annually. Independent and sex-specific risk factors for asthma diagnosis were assessed by using multivariable logistic regression models. RESULTS: In our cohort, 24.6% (42/164) of the children were diagnosed with asthma by 9 years of age. The mean ± standard deviation age of asthma diagnosis was 29.5 ± 4.5 months; 79.5% had a diagnosis of asthma at <4 years of age. In girls, any breast-feeding at 6 months was associated with a reduced risk of asthma (odds ratio [OR] 0.21 [95% confidence interval CI, 0.05–0.86]) and obesity at 2 years of was associated with increased risk for asthma (OR 12.14 [95% CI 2.79–53.05]). Exposure to environmental toxins and consumption of sugar-sweetened beverages were associated with a risk for asthma diagnosis after 4 years of age. CONCLUSION: In our high-risk Latino cohort, obesity was associated with asthma development in the girls. In addition, an asthma diagnosis after 4 years of age may be related to environmental toxin exposure and early consumption of sugar-sweetened beverages compared with an earlier diagnosis.